2016
DOI: 10.1002/stem.2321
|View full text |Cite
|
Sign up to set email alerts
|

Human Stem Cells Overexpressing miR-21 Promote Angiogenesis in Critical Limb Ischemia by Targeting CHIP to Enhance HIF-1α Activity

Abstract: Critical limb ischemia (CLI) is a severe blockage in the arteries of the lower extremities. However, the effective and optimal treatment for CLI remains to be elucidated. Previous therapeutic research is mainly focused on proangiogenic growth factors administrations. Recently, miR-21 has been revealed to play a crucial role in angiogenesis. Thus, we hypothesize that miR-21 over-expression in human umbilical cord blood-derived mesenchymal stem cells (UCBMSCs) can effectively treat CLI. Herein, UCBMSCs were tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 58 publications
2
33
0
Order By: Relevance
“…Relevant to the present study, miR-21 has been shown to play a vital role in vessel sprouting by regulating both HIF-1a and VEGF (55). It has also been shown that overexpression of miR-21 in mesenchymal stem cells resulted in an increase in proliferation, migration, and angiogenesis in vitro and increased neovascularization in a critical limb ischemia model (67). Herein, we demonstrate that in response to biomaterial culture, miR-21 levels are elevated in both CD34 + cells and the EVs they secrete.…”
Section: Discussionsupporting
confidence: 74%
“…Relevant to the present study, miR-21 has been shown to play a vital role in vessel sprouting by regulating both HIF-1a and VEGF (55). It has also been shown that overexpression of miR-21 in mesenchymal stem cells resulted in an increase in proliferation, migration, and angiogenesis in vitro and increased neovascularization in a critical limb ischemia model (67). Herein, we demonstrate that in response to biomaterial culture, miR-21 levels are elevated in both CD34 + cells and the EVs they secrete.…”
Section: Discussionsupporting
confidence: 74%
“…The local shortage of dissolved oxygen would upregulate expression levels of certain hypoxic proteins, e.g., MMP9, VEGF, MIF, PGK1, HIF1A, LDHA, TWIST, HGF, FGF, etc. [52,53,54,55,56,57]. Yet, none of these proteins were found to be upregulated in the Fs samples.…”
Section: Resultsmentioning
confidence: 97%
“…Increasing studies also indicated that MSCs derived angiogenic proteins could regulate the neoangiogenesis injury tissue for promoted wound healing process. Recently study also proved that miR‐21 overexpressed MSCs can effectively induce angiogenesis potential via promoting HIF‐1a activity . In the present study, in order to understand the mechanism of miR‐21 modified ADSCs in counteract urethral stricture formation, we examined the expression levels of some angiogenic genes, such as VEGF, HIF‐1a and SDF‐1a.…”
Section: Discussionmentioning
confidence: 82%
“…Recently study also proved that miR-21 overexpressed MSCs can effectively induce angiogenesis potential via promoting HIF-1a activity. 24 In the present study, in order to understand the mechanism of miR-21 modified ADSCs in counteract urethral stricture formation, we examined the expres- Together, these results suggested that ADSCs transplantation could effectively improve the healing and reconstitution of the urethra tissue to counteract US formation, and the miR-21 modification via lentiviral transfection can increase the therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 90%